Perancangan dan Implementasi Aplikasi E-Library Berbasis Dekstop di Sekolah SMPN 3 Lamasi - Rahmadani Rahmadani; Ruhamah Ruhamah; Suparman Suparman (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to design and implement a desktop-based e-library application at SMPN 3 Lamasi to simplify the management of library data, including books, borrowing, returning, visitors, and catalog records. The application is also equipped with reporting features that support library administrative needs. The development method used was Research and Development (R&D) with the Waterfall model, which consists of five stages. The first stage, Requirements Definition, involved gathering system requirements through observation, interviews, documentation, and literature review. The second stage, System and Software Design, included system design using Unified Modeling Language (UML). The third stage, Implementation and Unit Testing, involved coding the application with the Java programming language and performing initial testing on each module. The fourth stage, Integration and System Testing, ensured that all application components functioned correctly using the black-box testing method. The final stage, Operation and Maintenance, included deploying the application and maintaining it when errors occurred during usage. After completing all development stages, the application was validated by three experts. The first validator gave a score of 4.86, the second gave 4.56, and the third gave 4.95. The average validation score was 4.77, which falls into the “very good” category. The evaluation results indicated that the application fulfilled functional requirements and operated smoothly without significant errors. In conclusion, the desktop-based e-library application developed in this study successfully meets the operational needs of the library at SMPN 3 Lamasi. All features, including book data management, borrowing and returning transactions, visitor records, catalog management, and reporting, can be accessed and used effectively. Furthermore, the system has been proven to improve the effectiveness and efficiency of library management while supporting digital transformation in school library services.